PENGARUH PARTISIPASI ANGGARAN, PENEKANAN ANGGARAN, KOMITMEN ORGANISASI, KOHESIVITAS KELOMPOK, DAN ASIMETRI INFORMASI TERHADAP KESENJANGAN ANGGARAN (Studi Empiris pada SKPD Kabupaten Kampar) - Yafie Riandalas; Muhammad Rasuli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This research was carried out on a case study on the sectors in the district in order to test whether Kampar with budgetary participation, push budget, organizational commitment, group cohesiveness and information asymmetry affect the budget gap in preparing the budget. The population in this study is the official echelon III and IV, including heads of state / field and head subsections / subfields that works in SKPDs Kampar District Government. To analyze the data, in this study used multiple linear regression. The first hypothesis of the study results indicate that the effect on the Budget Participation Budgetary Slack. The second hypothesis testing results show that the emphasis of the Budget does not affect the Budgetary Slack. The third hypothesis testing results show that the effect on the information Organizational Commitment Budgetary Slack. The fourth hypothesis testing results show that the effect on the Group Cohesiveness Budget Gaps. This test proved the fourth hypothesis which states that the effect on the Group Cohesiveness Budgetary Slack. And the fifth hypothesis testing results show that the information asymmetry affect the Budgetary Slack.Keywords: Participation Budget, Budget Emphasis, Organizational Commitment, Group Cohesiveness and Information Asymmetry Against Budgetary Slack